The Impact of Financial Development on Unemployment: The Case of the People’s Republic of China (PRC) - Liu Yixin; Naziatul Aziah Mohd Radzi; Ma Mengqi; Normaizatul Akma Saidi (ETIKONOMI, 2024)
Research Originality: As a populous country with a population of 1.4 billion, China faces the imperative issue of employment. This paper focuses on the impact of financial credit and financial deposits on different levels of unemployment in an attempt to analyse the unemployment problem in China.Research Objectives: The paper explores the impact of financial development on unemployment in China.Research Methods: Using panel data from 31 provinces and cities in China (spanning from 2007 to 2021), categorizing unemployment situations, employing quantile regression models to assess the impact of financial development on different levels of unemployment in China.Empirical Results: The findings indicate a negative correlation between financial development and unemployment levels in China. The study reveals that financial credit significantly impacts unemployment in provinces where the economy is higher than average GDP. However, in regions where the economy is lower than average GDP, the impact of financial deposits on unemployment is significant.Implications: This study establishes that the adoption of financial expansionary policies by the government can reduce unemployment and help guide the formulation of more precise and effective economic policies.JEL Classification: G21, E24, C33, O53How to Cite:Yixin, L., Radzi, N.A.M., Ma, M., & Saidi, N.A., (2024). The Impact of Financial Development on Unemployment: The Case of the People’s Republic of China (PRC). Etikonomi, 23(2), 353 – 368. https://doi.org/10.15408/etk.v23i2.37997.